EVALUASI PENYUSUNAN LAPORAN KEUANGAN PADA TOKO DAILY LIFE STORE BERDASARKAN SAK EMKM - Heriyanto3, Diana Auliya Rahman1 Mardiana2 (EKONOMIA, 2021)
The purpose of this research is to know and evaluate the recognition, measurement, presentation, and application in the financial statements of the Daily Life Store. In accordance with the objectives of this study, the subject matter put forward "Is the recognition, measurement, presentation, and disclosure in the financial statements of the Daily Life Store Stores in accordance with the SAK EMKM Year 2018? "The theoretical basis used is the theoretical basis regarding financial accounting and SAK EMKM Year 2018. Based on these main problems, the following hypothesis is proposed: " The preparation of financial reports at the Daily Life Store is deemed not in accordance with the 2018 SAK EMKM. "Based on the results of the analysis that has been stated previously, it can be seen that the evaluation of the preparation of financial statements at the Daily Life Store is not suitable and is not in accordance with the SAK EMKM Year 2018. So that the hypothesis is rejected and accepted. It is expected that the Daily Life Store applies an accounting treatment that includes recognition, measurement, presentation and disclosure in accordance with SAK EMKM so that it can provide convenience in preparing financial reports.